2014
DOI: 10.1186/s13054-014-0624-8
|View full text |Cite
|
Sign up to set email alerts
|

Fluid balance, intradialytic hypotension, and outcomes in critically ill patients undergoing renal replacement therapy: a cohort study

Abstract: IntroductionIn this cohort study, we explored the relationship between fluid balance, intradialytic hypotension and outcomes in critically ill patients with acute kidney injury (AKI) who received renal replacement therapy (RRT).MethodsWe analysed prospectively collected registry data on patients older than 16 years who received RRT for at least two days in an intensive care unit at two university-affiliated hospitals. We used multivariable logistic regression to determine the relationship between mean daily fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 24 publications
7
89
0
2
Order By: Relevance
“…Silversides et al . [18] demonstrated fluid balance during dialysis as a predictor of mortality in AKI. Our results also show a correlation of fluid balance during dialysis with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Silversides et al . [18] demonstrated fluid balance during dialysis as a predictor of mortality in AKI. Our results also show a correlation of fluid balance during dialysis with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study [19] showed that there was no significant association of fluid overload with dialysis dependence (OR, 0.72; 95% CI, 0.38 to 1.35).…”
Section: Kidney Recoverymentioning
confidence: 92%
“…ventilation-free days, and another study [19] presented the relationship between fluid overload and RRT dependence.…”
Section: Eligible Studiesmentioning
confidence: 98%
See 2 more Smart Citations